The Chinese dream: China-Africa educational exchanges - Lam, K. (COOPEDU IV - Cooperação e Educação de Qualidade: Livro de Atas, 2018)
Over the decades, the People’s Republic of China has rapidly expanded its educational investments and experiments in Africa. It has increased exponentially the number of scholarships for African students to cross oceans to attend Chinese universities. Also, specialized programmes continue to be designed specifically to attract African candidates. Meanwhile, groups of Chinese teachers and technicians are dispatched to Africa to educate and train people on the ground. In individual African countries, Chinese professionals are integrated in local schools, participating in social, cultural and educational activities. In many cases, the Chinese dream has become a viable alternative to American colleges or European universities, in terms of social prestige, practicality and future prospects. Questions can be asked about the plausible explanations for such massive Chinese educational investments. It will also be worth knowing the main decision-makers, participants and beneficiaries, the impact on African societies, on China-Africa relations and on international politics, etc. This discussion is part of the more general debate on African human resources education and training. It sees Africa as a dynamic, democratic and vast arena where diverse education models compete for legitimacy, popularity and sustainability. Chinese education is emerging as a strong proponent.